Pendidikan Lingkungan Hidup Di Pondok Pesantren Al-Hassan Pondok Gede Kota Bekasi - Ephy Syah Reza; Risal Rinofah; Ratih Kusumawardhani (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This research is motivated by environmental conditions that are increasingly disturbing caused by human actions. Therefore, to realize environmental awareness, environmental education is needed at various levels. The purpose of this study was to analyze environmental education at the Al-Hassan Modern Islamic Boarding School Pondok Gede, Bekasi. The method is a descriptive method which is intended to describe phenomena that exist in the form of scientific phenomena. The results of this study indicate that Al-Hassan Pondok Gede Modern Islamic Boarding School, Bekasi has carried out an environmental campaign that started around the islamic boarding school and eventually spread to the surrounding community. Some of the program carried out are the vision and mission of an environmentally friendly islamic boarding school, the rules and regulations that exist in the Al-Hassan Islamic boarding school Pondok Gede Bekasi prioritizing an attitude of caring for the environment.